Elevator Maintenance Management in Healthcare Facilities in Johor Bahru - Amorzam, Aina Natasha; Muslim, Rahmat; Mohd Sari, Kamarul Aini (Progress in Engineering Application and Technology, 2023)
Healthcare facilities need effective elevator maintenance management in order to give patients, visitors, and other hospital building users, such as healthcare professionals, with a quiet and secure elevator that delivers optimum comfort. To do this, hospital facilities must have efficient elevator maintenance management systems and services. Aside from maintaining elevator safety, building users must be happy with the quality of management services, especially those provided to tenants. The purpose of this study is to determine the perceived level of satisfaction and occupant expectations regarding the quality of elevator maintenance services provided in healthcare facilities, as well as to identify the primary challenges faced by elevator maintenance management and possible solutions to these challenges. To fulfil the primary goal, a questionnaire was developed, disseminated to a sample of respondents, and analysed using the SERVQUAL method. The results demonstrate that tenants’ expectations and satisfaction levels are high in terms of dependability, tangibles, and assurance factors. Meanwhile, the components of responsiveness and empathy got the lowest rankings. The analysis average index was generated to indicate the primary problems and potential recommendations for elevator maintenance management in order to maintain the elevator system in accordance with the defined priorities, and the results reveal that all methods are critical. As a result, it is feasible that each of the identified methods has its own set of objectives that must be considered.